Emerging Technology Services Provided by Nigerian Library and Information Science Professionals - Oyedokun, Siddiqah Olatope; Oduwole, Adebambo A.; Odunewu, Abiodun O.; Adekunmisi, Sowemimo Ronke (University of Dar es Salaam Library Journal, 2024)
Emerging technologies are revolutionizing practically every area of human endeavor. This invention has resulted in a significant shift in the way libraries operate all around the world. Recent library technologies, which varied from library 1.0 to library 5.0, provide evidence of this. It is anticipated that this breakthrough will draw the tech-savvy generation to the library; sadly, in Nigeria, the opposite is evident. Based on this, the study looked at services based on emerging technologies that librarians and information scientists in Nigerian libraries provided. The study's population consisted of 45 attendees from the 2019 IT Section of the Nigerian Library Association Workshop, and it used a survey research design. Out of the 45 copies of the administered questionnaire that were recovered, only 38 were deemed relevant for the investigation. There were two sections to the questionnaire. Section B aimed to gather information on emerging library services offered and obstacles to their implementation, whereas Section A sought to clarify demographic data. The study's conclusions were computed using descriptive statistics. The survey found that practitioners provide a wide range of library services based on developing technology. According to the survey, there is a dearth of services based on emerging technologies, such as cloud computing, gaming, and the Internet of Things. The survey also found that among other difficulties, practitioners deal with erratic electricity and poor internet service provision. It was concluded that practitioners would maximize the use of emerging technologies if sufficient attention was given to the issues impeding their use in the delivery of library services. Recruitment of more personnel and provision of alternative power supplies were among the recommendations made in the study.